2011
DOI: 10.1016/j.neuropsychologia.2010.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning the components of visuomotor adaptation to prism-altered distance

Abstract: While the mechanisms of short-term adaptation to prism-altered apparent visual direction have been widely investigated, the processes underlying adaptation to prism-altered perceived distance are less well known. This study used a hand-pointing paradigm and exposure with base-out prisms to evaluate the relative contributions of sensory (visual and proprioceptive) and motor components of adaptation to perceived-distance alteration. A main experiment was designed to elicit adaptation at the sensory and motor lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 86 publications
1
16
0
Order By: Relevance
“…Note that a discrepancy between seen and felt hand positions is inherent to prism exposure and that such a discrepancy can induce sensory (visual and proprioceptive) adaptation (Harris, 1963; Redding et al, 2005; Priot et al, 2011). Several studies have shown that a minimum movement duration of 1 s or more is required for prism adaptation induced by visual-proprioceptive conflict (for a review, see Redding and Wallace, 1992b).…”
Section: Methodsmentioning
confidence: 99%
“…Note that a discrepancy between seen and felt hand positions is inherent to prism exposure and that such a discrepancy can induce sensory (visual and proprioceptive) adaptation (Harris, 1963; Redding et al, 2005; Priot et al, 2011). Several studies have shown that a minimum movement duration of 1 s or more is required for prism adaptation induced by visual-proprioceptive conflict (for a review, see Redding and Wallace, 1992b).…”
Section: Methodsmentioning
confidence: 99%
“…If the mismatch is easily resolved in motor coordinates (e.g., always activate the biceps more strongly, regardless of the target's position), the movement plan can be updated such that we successfully reach the targets (e.g., Baraduc and Wolpert 2002;Burge et al 2008;Galea and Miall 2006;Hinder et al 2010;Körding and Wolpert 2004;Krakauer 2009;Saijo and Gomi 2010;Tseng et al 2007; Wang and Sainburg 2005;Wei and Körding 2009). If the mismatch is more easily resolved in sensory coordinates (e.g., the visual position is rightward of the proprioceptive position regardless of the movement direction), the conflict can be resolved by updating the way in which sensory information is interpreted (Baraduc and Wolpert 2002;Block and Bastian 2012;Priot et al 2010; Wallace 1988, 2006).…”
mentioning
confidence: 99%
“…The functional relationship between actual and estimated target distances was analyzed using a linear model (Ebenholtz 1981;Mon-Williams and Tresilian 1999;Priot et al 2010Priot et al , 2011. For each subject and each condition, the relationship between the pointing distance (dependent variable) and the actual (physical) target distance (independent variable) was fitted with a line, using a leastsquares criterion.…”
Section: Discussionmentioning
confidence: 99%
“…These authors ascribed the observed distance aftereffects to a visual calibration: The prism-induced conflict between altered vergence and unaltered distance cues gave rise to a recalibration of the mapping between the vergence signal and egocentric perceived distance. Priot et al (2011) found that visual calibration and EMP both contribute to adaptation to prism-induced alteration of perceived distance. In contrast to visual recalibration, EMP develops in response to sustained fusional vergence demand and does not require any cue conflict.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation